The complete chloroplast genome sequence of Ludisia discolor from Hainan of China. Issue 2 (3rd July 2019) - Yu, Xia; Xie, Tai-Xiang; Liu, Bin; Zhang, Di-Yang; Liu, Xue-Die; Ai, Ye; Liu, Zhong-Jian
Abstract: Ludisia discolor is one of the most important ornamental and medicinal orchids. To improve our understanding of the evolution of chloroplast, we resequenced complete chloroplast (cp) genome of L. discolor from Hainan, China. The cp genome sequence of L. discolor of Hainan was 153, 324 bp in length, with a large single-copy (LSC) region of 82, 922 bp, a small single-copy (SSC) region of 17, 258 bp, and a pair of inverted repeats (IR) regions of 26, 572 bp. Complete chloroplast genome contain 132 genes, there were 86 protein-coding genes, 38 tRNA genes and eight rRNA genes. The phylogenetic tree showed that L. discolor of Hainan is sister to L. discolor (unknown distributed region). Their cp genomes have same gene number but different in length of genome, indicating high conserved among them.